Validity of dynamic prediction model for oxygen uptake during supra maximal intermittent load exercise - Takahashi, S.; Chiba, T.; Ishii, H.; Nishijima, T. (International Journal of Sport & Health Science, 2005)
The purpose of this study was to determine the validity of a dynamic prediction (DP) model that predicts oxygen uptake (VO2) during supra maximal intermittent (SMI) exercise based on non-linearity of VO2 dynamics in comparing a heart rate (HR) model. Five male participants (201 yrs) performed incremental exercise test used by cycle ergometer for the aim of developing individualized HR- VO2 and workload- VO2 regression equations. The DP model was defined as a first order system to workload- VO2 relationship. Participants then completed SMI test corresponding at 140 % VO2max while HR and VO2 data were collected continuously for 20 min. The HR model predicted VO2 during SMI test used by HR, while the DP model also predicted VO2 from workload. Predicted values (VO2) were compared with measured values (VO2) obtained via a metabolic measurement system. The DP model showed a significantly higher relationship with measured VO2 (R2 = 0.95, SEE = 149 ml/min) in comparison with the HR model (R2 = 0.83, SEE = 275 ml/min). The HR model showed significant systematic error (r = 0.41, P < .05), whereas the DP model did not (r = 0.06, P > .05). For comparison of prediction errors of both models, the error of the DP model (-1.38.8 %) was significantly smaller than the HR model (-8.016.5 %). The DP model also accurately estimated total energy expenditure. Therefore, the DP model is an accurate predictor of VO2 during supra maximal intermittent exercise.